Parental satisfaction with pediatric day-care surgery and its determinants in a tertiary care hospital - Cenita James Sam; Pavai A Arunachalam; Sivamani Manivasagan; T Surya (Wolters Kluwer Medknow Publications, 2017)
Objective: The objective is to assess the level of parental satisfaction of pediatric day-care surgery and its different determinants. Materials and Methods: This is a descriptive study performed in a tertiary care hospital in India among parents of pediatric day-care surgery patients from June 2013 to March 2015. The core questionnaire for the assessment of patient satisfaction for general day care (COPS-D) was used. Variables related to surgery, overall satisfaction, one open-ended question, and socio-demographic data were also collected. Calculated sample size was 121. Results: The mean and standard deviation of parental satisfaction were estimated in eight domains of day care (COPS-D) using Likert scale 1-5. Preadmission visit had a mean of 4.63 (0.52), day of surgery 4.65 (0.58), operating room 4.76 (0.51), nursing care 4.46 (0.79), medical care 4.89 (0.48), information 4.51 (0.68), autonomy 4.64 (0.56), and discharge 4.50 (0.72). In elder children, there was less satisfaction on the information and discharge domains. Overall satisfaction was good in 88% of patients and was less than satisfactory when they had significant pain. Conclusion: Perception of quality of pediatric day-care surgery was assessed with a questionnaire and was found to be good. Variables related to surgery such as pain may be included in the questionnaire for assessing satisfaction in the day-care surgery.